2018
DOI: 10.1093/ehjqcco/qcy036
|View full text |Cite|
|
Sign up to set email alerts
|

A meta-analysis of randomized controlled trials to compare long-term clinical outcomes of bioabsorbable polymer and durable polymer drug-eluting stents

Abstract: There were no differences in clinical outcomes between BP-DESs and DP-DESs over mid and long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A meta-analysis of randomized clinical trials looking at the long-term outcomes after DES implantation (3-5 years after PCI) did not identify any differences in the risk of cardiac mortality, ST, target lesion revascularization, target vessel failure and Re-infarction between BP-and PP-DES. 18 Recently, the long-term follow-up data from the ISAR-TEST 4 (Intracoronary Stenting and Angiographic Results: Test Efficacy of 3 Limus-Eluting Stents) trial did not show differences in clinical outcomes among patients treated with BP-or PP-DES up to 10 years. 19 The low rates of definite ST and restenosis in this study are remarkable and further corroborate the excellent safety performance of newer generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of randomized clinical trials looking at the long-term outcomes after DES implantation (3-5 years after PCI) did not identify any differences in the risk of cardiac mortality, ST, target lesion revascularization, target vessel failure and Re-infarction between BP-and PP-DES. 18 Recently, the long-term follow-up data from the ISAR-TEST 4 (Intracoronary Stenting and Angiographic Results: Test Efficacy of 3 Limus-Eluting Stents) trial did not show differences in clinical outcomes among patients treated with BP-or PP-DES up to 10 years. 19 The low rates of definite ST and restenosis in this study are remarkable and further corroborate the excellent safety performance of newer generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…Prior meta-analyses has established the superiority of BP-DES over BMS and rst generation DP-DES, and similar safety and e cacy pro les with secondary generation DP-DES [15,16] . The short-term follow-up results showed BP-DES had higher de nite ST rate [17] and mortality rate [16] .…”
Section: Discussionmentioning
confidence: 99%
“…On top of that, the study findings add further evidence supporting the use of SYNERGY BP‐DES in higher risk patients and lesions, but the evidence of its superiority lacks. A recent meta‐analysis of more than 15.000 patients enrolled in other randomized‐controlled trials had confirmed equivalent clinical outcomes between BP‐DES and DP‐DES over mid and long‐term follow‐up (up to 5 years) 5 …”
mentioning
confidence: 94%
“…A recent meta-analysis of more than 15.000 patients enrolled in other randomized-controlled trials had confirmed equivalent clinical outcomes between BP-DES and DP-DES over mid and long-term follow-up (up to 5 years). 5 In conclusion, the current TWILIGHT sub analysis is important because gives more light cues on the way of the reduction of TLF adding evidence on the importance of the pharmaco-invasive therapy that should not be uncoupled to solve the remaining challenges and improve the care of coronary artery disease patients.…”
mentioning
confidence: 99%